Dietary Supplementation of Endoxylanases and Phospholipase for Turkeys Fed Wheat-based Rations - Jr, A.A. Santos; Ferket, P.R.; Grimes, J.L.; Edens, F.W. (International Journal of Poultry Science, 2003)
The adverse effects of non-starch polysaccharides (NSP) on turkeys fed wheat-based diets may be alleviated by dietary supplementation of endoxylanase (to reduce the adverse effects of digesta viscosity) or phospholipase (to improve the digestibility of fat). BUTA toms were fed wheat-based diets containing one of 5 enzyme treatments: unsupplemented control, Natugrain Blend® (> 5,500 EXU/kg diet; NB), Lyxasan®-50 (> 2,250 EXU/kg diet; LX50), Lyxasan®-100 (> 5,500 EXU/kg diet; LX100), and Phospholipase (> 500 PLU/kg diet; PL) (BASF, Germany). Each treatment group was assigned to 8 pens containing 12 birds to evaluate growth performance (1-128 d), and 2 pens of 12 birds (excluding LX50) for the apparent metabolizable energy N-corrected (AMEn) and ileum viscosity determination (56-128 d). All enzyme treatments improved growth performance. In comparison to the control, dietary enzyme increased (P < 0.05) BW and decreased 1-128 d feed/gain (2.45 vs 2.37, P < 0.005). PL was most effective in reducing feed/gain during the starting phase and LX100 during the finishing phase, while NB had intermediate benefits throughout the experiment. PL increased AMEn from 9 to 12 wk, while NB and LX-100 resulted in the highest AMEn during the later finishing period. Viscosity was significantly higher for PL than the other treatments (13.5 vs 7.07 cP, P < 0.001). Growth performance and energy utilization of turkeys fed wheat-based diets can be significantly enhanced by phospholipase supplementation of starter feeds and endoxylanase supplementation of growing and finishing feeds. However, enzyme blends may provide a positive response regardless of turkey age.